Footprint: tourism information search based on mixed reality - Kasinathan, Vinothini; Mustapha, Aida; Yeap, Chee Seong; Zainal Abidin, Aida Zamnah (Insight - Indonesian Society for Knowledge and Human Development, 2017)
In the quest to provide better information seeking experience during travelling, this paper is set to design, build and trial a prototype tourism information search application based on mixed reality. This paper proposes “Footprint”, an android-based tourism information search application in a mixed reality environment, whereby it overlays tourism-related information on the image that the mobile phone camera is focused at. Using Footprint, the user would only need to point the mobile phone camera on a specific spot, and Footprint will overlay all in-formation on geo-tagged tourism objects as far as 30 meters away. The user is also able to filter search information based on the data source of information (such as Google or Wiki) or based on the category (such as Food or Landmark). It is hoped that this experience would one day become a trend, as when more reality-environments will be shaped into surreal, yet virtual alternatives through Internet of Things (IoT), and there will be more ubiquitous resource access through many devices, networks, and user content.